Computação desplugada nas escolas públicas: projeto de manual para o ensino do pensamento computacional com uso dos jogos de tabuleiros antigos e modernos - Gama, Bruno Gomes (2020)
The information society established by cyberculture brought with it Information and Communication Technologies (ICTs) for all social spheres, mainly for Education. What appears to be a revolution for pedagogical processes has shown to be a major gap in Public Schools in Brazil, as demonstrated in research by the Steering Committee. Therefore, we need to think of solutions that guarantee the digital citizenship of these students in environments where technology is not present. In this context, board games, based on the concept of computer science unplugged, appear as an alternative for the development of pedagogical practices that stimulate the construction of computational thinking without the presence of the computer. This paper aims to present a project based on the Instructional Design guidelines, using the ADDIE model, for the development of computational thinking in public schools, with the use of old and modern board games, in the context of computer science unplugged. To understand how this tool emerges as a solution to this problem, it was necessary to do an exploratory research about the history of the games and the concepts that encompass this area, as well as the application of Design Science Research to design the Project. Through this study we understand that the development of computational thinking through board games can be adopted as an educational practice capable of stimulating students' computing skills and competences, even without the presence of a computer.